Exergaming-based exercise program for people aged 50 years or older - Alexsander Guimarães; Vandrize Meneghini; Aline Barbosa (Revista Brasileira de Atividade Física e Saúde)
The purpose of the program "Video games for people aged 50 years or older" is to create free opportunities for older adults to engage in motivating and enjoyable physical activity, and to stimulate their functional fitness and cognition. This program has been carried out in the Universidade Federal de Santa Catarina since March 2014 and involves undergraduate and postgraduate students in the physical education department. The program follows the school semester, with approximately 36 people from the community participating each semester. The program consists of exercises that use video games that simulate sports activities, called exergames. Participants engage in a 60-minute session two or three times a week and on alternating days. Participants are evaluated at the beginning and end of each semester for functional fitness and cognition and the findings are presented to them. We expected that this program can be expanded and spread to other communities.